Covalent organic framework based microspheres as an anode material for rechargeable sodium batteries. Issue 34 (16th August 2018) - Patra, Bidhan Chandra; Das, Sabuj Kanti; Ghosh, Arnab; Raj K, Anish; Moitra, Parikshit; Addicoat, Matthew; Mitra, Sagar; Bhaumik, Asim; Bhattacharya, Santanu; Pradhan, Anirban
Abstract : Covalent organic frameworks (COFs) promise several benefits as materials in terms of gas adsorption, for use in optoelectronic devices, etc. Abstract : Covalent organic frameworks (COFs) promise several benefits as materials in terms of gas adsorption, for use in optoelectronic devices, etc. However, the energy storage ability of COFs has not been well studied, especially in sodium batteries. In this report, for the first time, a covalent organic framework (COF), TFPB-TAPT COF, is used as an anode with high capacity in sodium batteries. TheTFPB-TAPT COF exhibits an initial reversible capacity of 246 mA h g −1 and a capacity of 125 mA h g −1 is retained after 500 cycles. TheTFPB-TAPT COF further exhibits Na + ion storage capability at different current rates. The Na + ion storage viability of theTFPB-TAPT COF arises mainly because of its open ordered nanoporous framework, which provides reversible accommodation for ions. This work opens up a promising new approach for further utilization of COFs as electrode materials in rechargeable sodium batteries.